Epidemiological Characteristics of Postoperative Sepsis - Chen, Po-Yi (Open Med (Wars), 2019)
BACKGROUND: Postoperative sepsis is a major type of sepsis. Sociodemographic characteristics, incidence trends, surgical procedures, comorbidities, and organ system dysfunctions related to the disease burden of postoperative sepsis episodes are unclear. METHODS: We analyzed epidemiological characteristics of postoperative sepsis based on the ICD-9-CM codes for the years 2002 to 2013 using the Longitudinal Health Insurance Databases of Taiwan’s National Health Insurance Research Database. RESULTS: We identified 5,221 patients with postoperative sepsis and 338,279 patients without postoperative sepsis. The incidence of postoperative sepsis increased annually with a crude mean of 0.06% for patients aged 45–64 and 0.34% over 65 years. Patients with postoperative sepsis indicated a high risk associated with the characteristics, male sex (OR:1.375), aged 45–64 or ≥ 65 years (OR:2.639 and 5.862), low income (OR:1.390), aged township (OR:1.269), agricultural town (OR:1.266), and remote township (OR:1.205). Splenic surgery (OR:7.723), Chronic renal disease (OR:1.733), cardiovascular dysfunction (OR:2.441), and organ system dysfunctions had the highest risk of postoperative sepsis. CONCLUSION: Risk of postoperative sepsis was highest among men, older, and low income. Patients with splenic surgery, chronic renal comorbidity, and cardiovascular system dysfunction exhibited the highest risk for postoperative sepsis. The evaluation of high-risk factors assists in reducing the disease burden.